pengaruh reward, punishment dan disiplin kerja terhadap job satisfaction pada perawat instalasi rawat inap rumah sakit myria palembang - Alfiah Azizah; Hamid Halin; Shafiera Lazuarni (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to determine, analyze and prove the effect of reward, punishment and work discipline on job satisfaction in inpatient nurses at Myria Hospital Palembang. The theory used in this study is related to reward, punishment, work discipline and job satisfaction. A cross-sectional approach was used as a type of research with efforts to collect data using instruments in the form of questionnaires and data analysis techniques using the IBM SPSS 24 program. A total of 40 nurses at the inpatient installation of Myria Hospital with the characteristics of 32 women and 8 men became respondents in this study. The data analysis technique used is Multiple Linear Regression Analysis, Coefficient of Determination, F Test and T Test. Based on the tests carried out, the results obtained are that partially reward has a positive and significant effect on job satisfaction, partially punishment has a positive and significant effect on job satisfaction, partially work discipline has a positive and significant effect on job satisfaction and simultaneously reward, punishment and work discipline have a positive and significant effect on job satisfaction. Keywords : Job Satisfaction, Punishment, Reward, Work Discipline.